Data Assignments in Substantive Courses: Getting Undergraduates Excited and Interested in Data Science. - Atkeson, Lonna Rae (PS: Political Science & Politics, 2022)
The article presents the discussion on emphasizing and teaching to students giving the power of data in understanding the political and social world. Topics include learning about data science such as computer program, computer code, syntax files, output files, and data files; and introductory lecture covering the opening of dataset, the different data views, the concept of cases as rows and columns as variables.